ISLAMIC JOURNALISM ETHICS IN ADDRESSING THE PHENOMENON OF RELIGIOUS HOAXES ON SOCIAL MEDIA - Desiana Desiana; Hafsah Juni Batubara (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
The phenomenon of religious hoaxes on social media poses a serious threat to the social cohesion of a plural society because it touches the dimension of belief and easily arouses emotion. This study aims to map the phenomenon of religious hoaxes and their causes and impacts, to elaborate the principles of Islamic journalism ethics derived from the Qur'an and hadith, and to formulate their implementation as a strategy for countering religious hoaxes. It employs a qualitative approach with a library research design and a descriptive-analytical content analysis technique. The findings show that Islamic journalism ethics rests on four main principles, namely tabayyun (verification), shidq (truthfulness), 'adl (justice), and mas'uliyah (responsibility). The principle of tabayyun in QS Al-Hujurat verse 6 serves as an epistemological foundation that positions verification as a moral obligation consistent with modern journalism. Countering religious hoaxes requires a layered strategy combining the internalization of values at the individual level, MUI Fatwa No. 24 of 2017 at the normative level, the Journalistic Code of Ethics at the professional level, digital literacy at the community level, and regulation at the state level.